Imagining the Beyond: The Conceptualization of Duat between the Old and the Middle Kingdoms - Zago, Silvia.
This paper focuses on the evolution of the concept of Duat in the Old and Middle Kingdom funerary texts. This notion is already attested in the Pyramid Texts, which provide early but ambiguous references to it, seemingly identifying the Duat both with part of the sky and with a liminal domain located somewhere between earth and horizon, and endowed with regenerative power. Toward the end of the Old Kingdom, and with the emergence of the Coffin Texts, the depiction of the cosmos appears to have altered slightly. A better-defined universe was now sketched in the spells. Contrasted with the earth and the diurnal sky stood the Duat, which was, to some extent, described as including both nether sky and netherworld. This article traces the process of development of the concept of Duat within the broader frame of the ancient Egyptian funerary beliefs as attested in the Pyramid and Coffin Texts. Moreover, a brief analysis of a particular category of funerary objects popular in this period shows that the evolution in the conceptualization of the afterlife found in funerary texts underlies changes in material culture as well.   doi: http://dx.doi.org/10.5913/jarce.54.2018.a016